Surface seawater geochemistry results of IODP Expedition 389 (Hawaiian Drowned Reefs) - Jody M Webster; Ana Christina Ravelo; Hannah Grant; Margaret S Stewart; Marisa Rydzy; Erwan Le Ber; Nicola Allison; Ryuji Asami; Brian Boston; Juan-Carlos Braga; Logan Brenner; Xuefei Chen; et al. (PANGAEA, 2025)
Results of surface seawater (SSW) geochemistry analyses from International Ocean Discovery Program (IODP) Expedition 389 (Hawaiian Drowned Reefs). The offshore phase of this expedition took place between 2023-08-31 and 2023-10-31 onboard multipurpose vessel MMA Valour sailing from and to Barbers Point Harbor, Hawai extquotesinglei, USA, followed by the onshore phase from 2025-02-06 to 2025-02-26 at the Bremen Core Repository (BCR) hosted at MARUM – Center for Marine Environmental Sciences, University of Bremen. Sample collection was performed by hand-lowering a self-constructed water sampling device overboard, filling it with ambient seawater, and recovering it to the ship. The water sampling devices differed during leg 1 and leg 2 of the expedition. A total of 16 SSW samples were collected, with one SSW sample from each site except Site M0099, where two samples were recovered as this site has been revisited during leg 2. Each SSW sample was measured for alkalinity, pH, salinity, and ammonium on board the ship. Remaining analyses were performed later on in the onshore laboratories. For further methodological information see methods chapter in0.167emWebster, J.M. et al., 2025 https://doi.org/10.14379/iodp.proc.389.2025 ISD = improvised sampling device; NB = Niskin bottle; #0 = measurement result below detection limit